Can Native Geographical Range, Dispersal Ability and Development Rates Predict the Successful Establishment of Alien Ladybird (Coleoptera: Coccinellidae) Species in Europe? - Soares, António O.; Honěk, Alois; Martinkova, Zdenka; Brown, Peter M. J.; Borges, Isabel (Frontiers in Ecology and Evolution, 2018)
A list of alien ladybird (Coleoptera: Coccinellidae) species to Europe was prepared and the history and circumstances of their introductions were determined. Currently there are twelve alien ladybird species in Europe, originating from Australian, Oriental, Nearctic, Palearctic and Afrotropical regions. All of the species were intentionally released as biological control agents and most are coccidophagous species. The aphidophagous Harmonia axyridis is the only ladybird regarded as invasive in Europe. The main factors leading to successful establishment were food relationship, living in different habitats in different geographical regions and geographic origin. We found that successful invaders, in their native areas, showed adaptability to a wide range of conditions compared to non-invasive species. Larger aphidophagous alien ladybirds were found to develop as fast as native species. Characteristics that did not differ between native and alien species are thermal requirements for development, fecundity and body size. However, unlike other alien ladybirds, H. axyridis had higher potential dispersal ability.